Over a million students use our free study notes to help them with their homework
Complete the square.We want a quadratic we can simplify.Halve the linear term coefficient (6) and square it.Add it to the (x2+6x) term and subtract it from the 7.x2+6x+(6/2)2Answered by George B. • Maths tutor15844 Views
The aim is to find a common denominator, we first therefore cross multiply to get:(2(y-6)-(y+3))/((y+3)(y-6))After expanding the relevant brackets we are left with:(2y-12-y-3)/((y+3)(y-6))Which is simply:...
To find the value of w, let x = w and y = -32. Substitute these values into the equation of the curve, C: y = (2x-3)^5 => -32 = (2(w) - 3 )^5. Note: the symbol, =>, means "implies that." F...
Equation1: 2x - 2y = 20, equation 2: x + 4y = 5First method (subtraction):Multiply equation1 by 2: 4x - 4y = 40Add the two equations together canceling out the y unknowns: 4x + x = 40 + 5Solve for ...
Firstly we can use the difference rule to split f'(x) into three components which we can consider separately. Then using the knowledge that the integral of x^n is 1/(n+1)*x^(n+1) we get the expression for...
←
530
531
532
533
534
→
Internet Safety
Payment Security
Cyber
Essentials